METHOD OF TEATCHING IN PHYSICAL EDUCATION: A STUDY OF PRACTICAL PEDAGOGICAL IN THE MUNICIPAL SCHOOLS OF MARECHAL CÂNDIDO RONDON (Fiep Bulletin - online, 2014)
ABSTRACT: This text was elaborated from a survey-action and had as its aim to investigate the Physical Education teacher's practices pedagogies of Elementary School beginning levels, as well to guide them towards a Relational Pedagogy. The field survey consisted of two phases: in the first it was verified the teacher's attitude without the guide interference, and, in a second phase, after being guided to sharing pedagogies. The survey results were rewarding, for all the study participants had significant changes in favor of the Relational Pedagogy.
Keywords: Child; Pedagogies; Physical Education